Nrf2 suppresses macrophage inflammatory response by blocking proinflammatory cytokine transcription - Eri H. Kobayashi (Nature Portfolio, 2016)
Nrf2 is a transcriptional activator of oxidative stress response genes. Here the authors show that Nrf2 binds to promoters of proinflammatory genes and interferes with their transcriptional upregulation in LPS-stimulated macrophages independently of its role in regulation of reactive oxygen species.